The effect of microstructure and solution concentration on the resistance of austenitic stainless steel - 246388 Yap, Sook Mee (Sekudai : UTM, 1998)
Project Paper (Bachelor of Mechanical Engineering) - Universiti Teknologi Malaysia, 1998